Impactos da pandemia na distribuição cinematográfica: estudo de caso das estreias de dois longas-metragens da Vitrine Filmes - Lage, Adhemar Soares (2023)
This research seeks to investigate the phenomenon of joint distribution (day-and-date) and the release of films on video on demand (VOD) platforms and movie theaters of the films A Febre (2020) and Alvorada (2021), which took place in the early years of the Covid-19 pandemic. Distribution is an important step in the film production chain, responsible for the link between work and audience. A case study of two feature films was carried out to achieve the objective, with a theoretical survey on the field, production chain, and distribution. In collecting data for analysis, information about the box office, rental platforms, and interviews with the distributors and directors of Vitrine Filmes of the feature films were used. Through this dissertation, it was possible to identify the transformations, advantages, and disadvantages of the joint premiere and analyze the pandemic's impacts on the distribution of national films.